Assessing Multidimensional Energy Poverty and Its Economic Impact on N11 Countries: Mediating Role of Energy Efficiency - Hieu, Vu Minh; Hien Phan, Thi Thu; Trung, Lam Minh (Frontiers in Energy Research, 2022)
This study seeks to estimate energy poverty using a multidimensional and wide-ranging category of indicators via the GRA-SRA approach. The study entails a case study analysis of the N-11 nations utilizing data from 2000 to 2017. Thus, a formulation of multidimensional energy poverty indexes of multidimensional indicators crosswise three dimensions is carried out. Energy availability, energy affordability, and energy cleanability, with regard to the N11 nations, are taken into account. The findings reveal that total energy poverty has progressed. We discover that Bangladesh (0.65) and Pakistan (0.47) are at risk concerning energy poverty, whereas the Philippines (0.36), Indonesia (0.33), and Vietnam (0.28) are less exposed to energy poverty. The relative changes in energy poverty are discovered among the N11 nations, where South Korea witnessed a consistent advancement in energy poverty, whereas Iran displayed a reduced trajectory and a vacillating trend. The findings indicate that the energy sources utilized for warming homes are essential within the scenario of energy poverty and inequality. Contrary to traditional steps, we assess the multidimensional energy poverty at the national level instead of the depths of gravity of energy poverty specifically for the energy-poor as against the whole population.